The new professional's toolkit - Ruddock, Bethan (London : Facet Pub., 2012)
'The Toolkit aims to support new professionals and help them develop themselves and their services. It draws together case studies on various aspects of Library and Information work, aimed at new professionals and supported by exercises, hints and tips, and further reading.'--Companion website.
Includes bibliographical references and index.
Keywords: Information scientists -- Vocational guidance -- Handbooks, manual, etc; Success in business -- Handbooks, manuals, etc; Professional employees -- Handbooks, manual, etc